EDUKASI PENDAMPINGAN BELAJAR SD, PENYULUHAN STUNTING, MEDIA INTERAKTIF DAN PELATIHAN MICROSOFT OFFICE - Nur Haida; Multazam Multazam; Veronika Kune; Ermelinda Be’i; Arham Rahim (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service activity was carried out with the aim of improving the quality of basic education, increasing awareness of the importance of health, and developing technological skills in the school and community environment. The program consists of four main activities, namely: (1) learning assistance for elementary school students, (2) counseling on stunting for parents and local residents, (3) application of interactive media in the learning process, and (4) basic training in the use of Microsoft Office applications. The methods used include delivering material through lectures, discussions, demonstrations, direct practice, and ongoing assistance. The results of the implementation show an increase in student motivation and learning outcomes, an increase in community understanding of stunting prevention, an increase in active student involvement in interactive media-based learning, and the development of basic skills of the community and teachers in operating Microsoft Office. Thus, this program makes a real contribution to improving the quality of education, health, and teachers' digital capabilities.